Amazon Biobank: a Blockchain-based Genomic Database for Bioeconomy - Kimura, Leonardo T.; Simplício Jr, Marcos A. (Anais Estendidos do Simpósio Brasileiro de Sistemas de Informação (SBSI); 2024: Anais Estendidos do XX Simpósio Brasileiro de Sistemas de Informação, 2024)
The bioeconomy, an industrial production model based on biological resources and sustainable development, can be considered an emerging opportunity for biodiversity-abundant regions, such as the Amazon rainforest. However, existing genomic repositories lack data traceability and economic benefit-sharing mechanisms, resulting in limited motivation for data providers to contribute. To address this challenge, we present Amazon Biobank, a community-driven genetic database. By leveraging blockchain and peer-to-peer (P2P) technologies, we enable distributed and transparent data sharing; meanwhile, by using smart contracts directly registered in the system, we enforce fair benefit-sharing among all system participants. Moreover, Amazon Biobank is designed to be auditable by any user, reducing the need for trusted system managers. To validate our approach, we implemented a prototype using Hyperledger Fabric and BitTorrent and evaluated its performance. Our results show that the prototype can support at least 400 transactions per second in a small network and that it can be further improved by adding new nodes or allocating additional computational resources. We expect that Amazon Biobank will serve as a vital tool for collaborative biotechnology research, fostering sustainable development in high-biodiversity regions.